2008
DOI: 10.4103/1596-3519.55687
|View full text |Cite
|
Sign up to set email alerts
|

Audit of oral and maxillofacial surgical conditions seen at Port Harcourt, Nigeria

Abstract: Background:The worldwide pattern of oral and maxillofacial surgical conditions has been rarely reported despite its significance in head and neck medicine. The Niger Delta region comprises 9 of the 36 states in the Federal Republic of Nigeria. There are scanty reports on oral and maxillofacial surgical diseases from the region despite its 95% contribution to Nigeria's oil-revenue. Methods: This retrospective survey of oral/maxillofacial surgical cases seen at a referral center in Port Harcourt, a city in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 15 publications
11
19
1
Order By: Relevance
“…The observed prevalence of 80.3%, while comparable to the 83.3% obtained by Adebiyi et al from Lagos, Nigeria 16 is much higher than results of similar studies from Nigeria. 2,17,18 Our observed prevalence of ameloblastoma (n=53; 80.3%) in our 11 year study period was comparable to that of Adebayo et al 10 (n=12; 80%) recorded in a period of 5 years from the same geopolitical zone in southern Nigeria. One reason adduced for the relatively high frequency of occurrence is the heterogeneous epithelial origin of ameloblastoma.…”
Section: Discussionsupporting
confidence: 81%
“…The observed prevalence of 80.3%, while comparable to the 83.3% obtained by Adebiyi et al from Lagos, Nigeria 16 is much higher than results of similar studies from Nigeria. 2,17,18 Our observed prevalence of ameloblastoma (n=53; 80.3%) in our 11 year study period was comparable to that of Adebayo et al 10 (n=12; 80%) recorded in a period of 5 years from the same geopolitical zone in southern Nigeria. One reason adduced for the relatively high frequency of occurrence is the heterogeneous epithelial origin of ameloblastoma.…”
Section: Discussionsupporting
confidence: 81%
“…These numbers do not substantially deviate from other literature data (8,9). Our patients also had a similar age range.…”
Section: Discussionsupporting
confidence: 58%
“…Among them 1842 were males and 922 were females. The male to female ratio was 2:1; whereas it was 1.7:1 in a study by department of Dental Surgery, Military Hospital, Port Harcourt, Nigeria [3]. Maxillofacial injuries comprised of 36.32 % (n = 1004) of the total patients, out of them 69.72 % were mandible fractures [2], in other studies it showed higher incidence, 46.4 % [3], 55 % [4].…”
Section: Introductionmentioning
confidence: 99%
“…Between 2000 and 2004, department of Dental Surgery, Military Hospital, Port Harcourt, Nigeria [3], a referral centre for Niger's Delta region reported 86 patients who needed maxillofacial surgery. Out of 110 indications, 39 % were tumour and allied lesions, it was higher (21 % [4]) from another study of the same country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation